2022
DOI: 10.1039/d2bm01099b
|View full text |Cite
|
Sign up to set email alerts
|

Sustained release of chlorogenic acid-loaded nanomicelles alleviates bone loss in mouse periodontitis

Abstract: Periodontitis is a prevalent chronic inflammatory disease that destroys the periodontal supporting tissues, impinges on oral health, and is correlative with an increased risk of systemic disease. Currently, the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Huang, Xin found that in ammation in LPS-induced human gingival broblasts via CysLT1R/Nrf2/NLRP3 signaling is attenuated by chlorogenic acid [40]. Not singly, but in pairs, Li, Han, and his colleagues reported that the sustained release of chlorogenic acid inhibits alveolar bone resorption and prevents periodontitis progression in a mouse model [41]. Notably, a study investigated the effect of caffeine and chlorogenic acid on periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Huang, Xin found that in ammation in LPS-induced human gingival broblasts via CysLT1R/Nrf2/NLRP3 signaling is attenuated by chlorogenic acid [40]. Not singly, but in pairs, Li, Han, and his colleagues reported that the sustained release of chlorogenic acid inhibits alveolar bone resorption and prevents periodontitis progression in a mouse model [41]. Notably, a study investigated the effect of caffeine and chlorogenic acid on periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al found that inflammation in LPS‐induced Human gingival fibroblasts via CysLT1R/Nrf2/NLRP3 signaling is attenuated by chlorogenic acid [37]. Not singly, but in pairs, Han Li and his colleagues reported that the Sustained release of chlorogenic acid inhibits alveolar bone resorption and prevents periodontitis progression in a mouse model [38]. What is worth mentioning that a study investigated the effect of caffeine and chlorogenic acid on periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…36 Drug release properties of CGA CGA exhibits several pharmacological properties (e.g., strong water solubility, short half-life and low bioavailability), which only reached (1.3 ± 0.6) h under the effect of the relatively short elimination half-life (t 1/2 ). [41][42][43] Therefore, it is crucial to select an appropriate drug carrier, such as hydrogel microspheres, that can create a porous network to exhibit the high resolution control of spatial tissue and effectively release the drug in a controlled manner. [44][45][46] Then, the CGA-loaded CGM sample was evaluated as a drug delivery vehicle.…”
Section: Swelling and Degradation Of Microspheresmentioning
confidence: 99%